First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations mothers and young children, and to emphasise the value and dignity of Motherhood. c. EUGENICS.— The importance of Heredity and the transmission of hereditary defects. The selection of suitable and healthy partners in marriage. The importance of worthy and responsible parenthood. The care of Mental Defectives. d. FOOD.— Its constituents and proper proportion and value to the Human Body. Best methods of cooking, and effects of improper diet. e. ALCOHOL.— Its use and abuse ; its relation to disease and crime, and its physiological and environmental influences upon the human organism and race. f. HOUSING.— The importance of proper housing accommodation to health and morals. The need of sufficient ground space for every house. g. PHYSICAL EDUCATION.— The value of physical exercise and organised games, and their effect on mental and physical health. h. TUBERCULOSIS.— Showing the modern methods of cure and of prevention of tuberculosis in the home, the factory and the workshop. i. VENEREAL DISEASE.— The furtherance of the educational campaign against this scourge. j. LEGISLATION AND HEALTH. k. INDUSTRIAL HYGIENE.— Choice of occupation — Its Relation to Individual Health. 10. The League shall promote the establishment of Recreation Clubs and proper facilities for their development. 11. An object of the League shall be the establishment of a Relief Fund for the benefit of physical defectives. To obviate confusion or overlapping, such Fund should be used where possible, in conjunction with, and supplementary to, the administrative work of Local Statutory Bodies dealing with Health in any of its aspects. 12. It shall be the duty of the League in its corporate body, and also the duty of every member of the League, to work for the betterment of all housing conditions, food conditions, working conditions and social conditions. It is the hope of the League that the Mayors, Corporations and other Local Authorities of the Empire will open Branches of the People's League of Health on the lines indicated above. The Nation has constantly been urged to stop wasting wealth and to organise all resources for increased production. But the real source of wealth lies in Motherhood, the Cradle and the Healthy Nurture of Children, and it is there that waste is irreparable. Increased production of wealth depends upon achieving and maintaining a higher standard of national health. The immediate obstacle is inefficiency due to preventable disease. Only by means of education can this obstacle be removed. "It is better to erect a strong fence at the top of the cliff than to maintain a working ambulance at the bottom." 4 200/B/3/2/C693/1/71